Analisis Krisis Teori Komunikasi Barat Dalam Konteks Nilai-Nilai Islam - Ade Syifa Fauziah; Elsa Amelia; Ismail Mubarok (Jurnal Pendidikan Indonesia (JOUPI), 2023)
Islamic communication is a system of information exchange between Muslims that remains in line with the foundation of Islam, and is guided by the Qur'an and Hadith. In this era of advanced technology, there are many external and internal influences on the Islamic communication system, one of which is Western communication. The communication system refers to the principles and practices of communication that dominate in western cultural areas, especially in North America and Europe. This journal aims to conduct a critical analysis of Western communication theory and how it relates to Islamic values. The main focus of the research is to discover the extent to which Western communication theory can be adapted and harmonized in the context of Islamic values, as well as the extent to which the relationship between the two can be understood by qualitative critical analysis of the content of communication documents and literature that elaborates Islamic principles as well as Western communication theory. The final product of critical analysis suggests that it is possible for better integration between Western communication theory and Islamic values once it involves introducing important concepts and assessing their conformity with Islamic principles. The conclusion of this study provides a critical perspective and direction to develop a communication approach that aligns Western communication theory with Islamic values. The results of this study can help understand how communication theory is applied in societies influenced by these values.